Global insights into nitrogen losses and efficiency in rice, wheat, and maize cultivation - Chakraborty, Debashis; Ladha, Jagdish Kumar; Das, Bappa; Dharamvir Singh Rana; Gathala, Mahesh Kumar; Jat, Mangi Lal; Krupnik, Timothy J. (Elsevier, 2025)
Context: Nitrogen (N) use efficiency (NUE) and N losses in cereal systems are central to achieving the United Nations Sustainable Development Goals (SDGs) on food security and environmental sustainability. However, global variations in NUE across cereals, regions, and management conditions remain poorly quantified, especially in relation to the relative roles of synthetic and non-synthetic N inputs.